Effects of high-intensity intermittent priming on physiology and cycling performance - McIntyre, J. P. R.; Kilding, A. E. (Journal of Sports Sciences, 2015)
The pre-event warm-up or "priming" routine for optimising cycling performance is not well-defined or uniform to a specific event. We aimed to determine the effects of varying the intensity of priming on 3 km cycling performance. Ten endurance-trained male cyclists completed four 3 km time-trials (TT) on four separate occasions, each preceded by a different priming strategy including "self-selected" priming and three intermittent priming strategies incorporating 10 min of constant-load cycling followed by 5 × 10 s bouts of varying relative intensity (100% and 150% of peak aerobic power, Wpeak, and all-out priming). The self-selected priming trial (379 ± 44 W) resulted in similar mean power during the 3 km TT to intermittent priming at 100% (376 ± 45 W; -0.7%; unclear) and 150% (374 ± 48 W; -1.5%, unclear) of Wpeak, but significantly greater than all-out priming (357 ± 45 W; -5.8%, almost certainly harmful). Differences between intermittent and self-selected priming existed with regards to heart rate (6.2% to 11.5%), blood lactate (-22.9% to 125%) and VO2 kinetics (-22.9% to 8.2%), but these were not related to performance outcomes. In conclusion, prescribed intermittent priming strategies varying in intensity did not substantially improve 3 km TT performance compared to self-selected priming.